2003
DOI: 10.1002/eji.200324176
|View full text |Cite
|
Sign up to set email alerts
|

The influence of CD95L expression on tumor rejection in mice

Abstract: Many tumors express the death ligand CD95L (CD178, APO-1L, FasL) and can kill activated T cells in vitro. This may enable the tumor cells to suppress anti-tumor immune responses, a phenomenon called "tumor counterattack". Preliminary evidence of tumor counterattack in human tumors exists. However, CD95L-expressing tumors are rapidly rejected in mice. In order to clarify this controversial situation we investigated whether the level or the time point of CD95L expression might be critical factors determining tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Previous reports using magnetic bead-isolated CD4 ϩ CD25 ϩ T cells showed CD95 expression on human and murine CD25 ϩ cells (7,16). We confirmed these data on CD4 ϩ T reg FACSsorted for very high CD25 expression.…”
Section: Cd4supporting
confidence: 89%
See 1 more Smart Citation
“…Previous reports using magnetic bead-isolated CD4 ϩ CD25 ϩ T cells showed CD95 expression on human and murine CD25 ϩ cells (7,16). We confirmed these data on CD4 ϩ T reg FACSsorted for very high CD25 expression.…”
Section: Cd4supporting
confidence: 89%
“…CD95L was produced as a leucine zipper-tagged ligand of CD95 (15,16). The anti-CD3 Ab OKT3 and the agonistic monoclonal anti-CD95 Ab (anti-Apo-1) were purified from hybdridoma supernatants by protein A affinity purification (15 …”
Section: Abs and Reagentsmentioning
confidence: 99%
“…Current evidence for the role of Fas/FasL-mediated apoptosis in T suppressor homeostasis is inconclusive. Although T suppressor cells express Fas constitutively (39,40), they are resistant to anti-Fas Ab-mediated apoptosis (41). In contrast, it was recently reported that whereas CD4 ϩ CD25 ϩ T suppressors were resistant to AICD via TCR-stimulation, they were uniquely sensitive to soluble CD95 ligand-mediated apoptosis in vitro (42).…”
Section: Cd25mentioning
confidence: 99%
“…For apoptosis induction, T cells were stimulated with a 1:10 dilution of a leucine zipper-tagged CD95 ligand (CD95L). 17,18 Annexin V Alexa Fluor 488 was purchased from Molecular Probes (Eugene, OR, USA) and propidium iodide (PI) was obtained from Sigma-Aldrich (St Louis, MO, USA). Unstimulated cells were incubated with CD95L-free control medium yielding spontaneous apoptosis of 15-30% in 20 h. Cell death was assessed by annexin V/PI costaining and forward-to-sideward-scatter profile.…”
Section: Cell Isolation and Sortingmentioning
confidence: 99%